1981
DOI: 10.1002/ana.410090606
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of optic neuritis with special reference to cerebrospinal fluid immunoglobuhs and measles virus antibodes

Abstract: Forty-eight patients with optic neuritis (ON), first seen in 1970 to 1973, were neurologically and neuroophthalmologically reexamined after 7 to 10 years. Twenty-seven patients (56%) had probable MS, and 9 (19%) had possible MS. During the attack of ON, the cerebrospinal fluid (CSF) samples and serum/CSF measles antibody ratios were studied. Twenty patients had increased relative immunoglobulin G (IgG) (% of total protein) in their CSF; 19 of these had probable or possible MS. However, 17 of 28 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 16 publications
2
5
0
2
Order By: Relevance
“…It is noteworthy that the CSF showed an increase of relative gammaglobulin level only in one case. An elevated gammaglobulin was seen in 42% of patients with acute ON in a Finnish series (25). As presented in that study, a normal CSF seems to mean a better prognostic value in regard to the risk of developing MS.…”
Section: + -supporting
confidence: 61%
See 1 more Smart Citation
“…It is noteworthy that the CSF showed an increase of relative gammaglobulin level only in one case. An elevated gammaglobulin was seen in 42% of patients with acute ON in a Finnish series (25). As presented in that study, a normal CSF seems to mean a better prognostic value in regard to the risk of developing MS.…”
Section: + -supporting
confidence: 61%
“…An elevated gammaglobulin was seen in 42% of patients with acute ON in a Finnish series (25). An elevated gammaglobulin was seen in 42% of patients with acute ON in a Finnish series (25).…”
Section: + -mentioning
confidence: 85%
“…Moulin D, Paty DW, Ebers GC: The predictive value of CSF electrophoresis in 'possible' multiple sclerosis. 14. 12.…”
mentioning
confidence: 99%
“…30 A previous study using an ELISA technique showed that the serum/CSF antibody ratio range for measles, rubella and mumps in patients with AMON were intermediate to those obtained in patients with CDMS and in control patients. 31 Furthermore, a decreased serum/CSF antibody ratio at onset of AMON implied a high risk of developing MS. 32 In our study, ®ve of 27 patients developed additional symptoms and signs of demyelinating disease within one year of follow up. All these patients had oligoclonal IgG bands, virus-speci®c oligoclonal IgG antibodies against one or more speci®c viruses, and abnormal MRI at onset of AMON.…”
Section: Discussionmentioning
confidence: 51%